2024
DOI: 10.1111/srt.13715
|View full text |Cite
|
Sign up to set email alerts
|

The causal relationship between atopic dermatitis and brain cancer: A bidirectional Mendelian randomization study

Yu Xin,
Tao Yuan,
Jun Wang

Abstract: BackgroundAtopic dermatitis ranks among the prevalent skin disorders. Research has indicated a potential association with brain cancer. Yet, establishing a direct causal relationship between atopic dermatitis and brain cancer continues to be challenging.Materials and MethodsWe extracted single nucleotide polymorphisms (SNPs) significantly associated with atopic dermatitis (sample size = 382 254) at a genome‐wide level from a large Finnish Genome‐Wide Association Study (GWAS) dataset (n cases = 15 208, n contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…15 However, one recent MR study has reported that AD might increase brain cancer risk. 42 Moreover, the identified studies on AD for LC risk were inconclusive. and found that subjects who reported a history of AD were inversely correlated with LC (OR: 0.73; 95% CI: 0.48−1.12).…”
Section: Discussionmentioning
confidence: 99%
“…15 However, one recent MR study has reported that AD might increase brain cancer risk. 42 Moreover, the identified studies on AD for LC risk were inconclusive. and found that subjects who reported a history of AD were inversely correlated with LC (OR: 0.73; 95% CI: 0.48−1.12).…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between inflammatory diseases and systemic malignancies remains unclear. 1 , 2 Inflammatory skin diseases are characterized by chronic inflammation, immune dysregulation, and altered cytokine profiles. 3 Chronic inflammation has been recognized as a hallmark of cancer, contributing to tumor initiation, promotion, and progression.…”
Section: Introductionmentioning
confidence: 99%